Analytical solution for pulsating laminar flow in easily penetrable rough channel - Гаева, Е. А.; Гаев, Е. А. (Proceedings of National Aviation University (archive), 1998)
Generalized is the problem of flow of viscous liquid in an infinitely stretching plane channel under the influence of periodically changing pressure in case that is near the channel walls there are layers with distributed mass force proportional to local velocity (easily penetrable roughness). According to analytical solution which is received in complex numbers built are changing in time and distributing across the channel velocities with or without the presence of easily penetrable roughness for two typical frequencies of pressure pulsation